Effectiveness of online GIS training on increasing professional competence of geography teachers - Diniy Antis Rizqiyyah Raihan; Somantri Lili (E3S Web of Conferences)
The change in the implementation of face-to-face learning to online during the Covid-19 pandemic requires teachers to adapt the learning system. In the Geographic Information Systems (GIS) subject, the delivery of GIS material to students often remains theoretical, lacking practical application. To address this, teacher selfdevelopment efforts are needed to support the competency improvement during the online class by participating in training. This study aims to analyze the effectiveness of online GIS training for geography teachers. The method used is descriptive analysis with a qualitative approach and data collection using literature review and interviews. The results found that teacher participation in training acts as a form of professional self-development, enhancing theacher’s knowledge and professional competence. During the pandemic, various trainings can be easier to follow, in addition to maintaining distance, online training can also bridge the barriers of distance and location of implementation. Online GIS training in particular can still improve teacher competence, but there are obstacles for some teachers who are lacking in managing information technology tools. The role of the presenters as well as the detailed training modules will greatly help the training objectives to be achieved.